Wagers’ ideas on iddaa who accommodate betting game - Coşkuner, Zeki; Çoban, Bilal; Devecioğlu, Sebahattin; Yıldırım, Eyyup (My University, 2013)
Many researchers who work on individuals’ participation to sports as spectators have dealt with factors which affect participation to sports as four main perspectives such as attraction of competition, economic factors, socio-demographic factors and spectators’ choices. Target population of the study is dealers and Internet cafés which accommodate wagers DDAA in Turkey. Sample of the study is consisted of 146 dealers of DDAA and Internet cafés managers from Elazıg, Ankara, Malatya, Diyarbakır, Sivas, Kahramanmaras, Gaziantep, Antalya, Kayseri and Giresun provinces. As a result, it is stated that “Children play betting games even with their pocket money.” item is at medium level “Medium” with (X=3,09) degree, “This game will soon be the most played one.” item is at top level “Most” with (X=3,69) degree, “Letting people earn money easily makes an important role to become widespread on betting game.” item is top level “Most” with (X=4.12) degree and “Playing DDAA needs accumulation of knowledge and continuous follow up thus I think that gamers deserve money what they get from DDAA betting game.” It is ensued that most of the people who go Internet Cafés consist of teenagers. However habitués of Internet Cafés have to be above 15 years old legally, it is remarked that this rule is always broken.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: İddaa; Betting; Gamble; Game; Football